2016
DOI: 10.1515/atd-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Civic Engagement and Environmental Sustainability in Teaching and Learning at Higher Education Institution in South Africa

Abstract: This article seeks to provide an outline the scope of professional teaching and learning activities and their connection to civic engagement and the achievement of environmental sustainability at Rhodes University and in Makana Local Municipality. Activities in the context of rainwater water harvesting and sanitation research are used as examples. The improved hydrogen-sulphide test kit was used as the tool for the assessment of microbial water quality between April and July 2016. An approach to the improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 8 publications
0
21
1
Order By: Relevance
“…The water is used to supplement the water requirements during a municipal potable water outage (Nhokodi et al, 2016). The current results suggested that the rainwater needs to be treated before human consumption and its microbial quality should be monitored regularly using previous reported approaches, e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The water is used to supplement the water requirements during a municipal potable water outage (Nhokodi et al, 2016). The current results suggested that the rainwater needs to be treated before human consumption and its microbial quality should be monitored regularly using previous reported approaches, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Three sampling sites with rainwater harvesting and storage tanks were identified around Rhodes University campus and were sampled on six occasions between April and July 2016 (Nhokodi et al, 2016). To eliminate any false negative results, all kits with sampled rainwater were incubated at 35-37 °C for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Eastern Cape Province and the Makana area are prone to droughts and are water-scarce areas (Nhaka, 2012; Tandlich et al, 2015). At the same time, water interruptions are a common occurrence (Nhokodi et al, 2016) and thus water quality problems can be expected to occur. The aim of this article is to examine the physico-chemical and microbial water quality from the various potable water sources in Makana.…”
Section: Introductionmentioning
confidence: 99%